2017
DOI: 10.3168/jds.2016-11261
|View full text |Cite
|
Sign up to set email alerts
|

Including nonadditive genetic effects in mating programs to maximize dairy farm profitability

Abstract: We compared the outcome of mating programs based on different evaluation models that included nonadditive genetic effects (dominance and heterozygosity) in addition to additive effects. The additive and dominance marker effects and the values of regression on average heterozygosity were estimated using 632,003 single nucleotide polymorphisms from 7,902 and 7,510 Holstein cows with calving interval and production (milk, fat, and protein yields) records, respectively. Expected progeny values were computed based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
65
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 44 publications
22
65
1
6
Order By: Relevance
“…In a simulated example, Toro and Varona ( 2010 ) compared random mating vs. mate selection with a model including dominance and found advantages that ranged between 6 and 22% of the expected response. Sun et al ( 2013 ), Ertl et al ( 2014 ), and Aliloo et al ( 2017 ) have confirmed these improvements with dairy cattle data. However, its implementation in livestock populations is limited because it must be taken into account that the accuracy of the prediction of a potential mate will be low and the advantage will be only relevant when traits have a large amount of non-additive genetic variance.…”
Section: Applications Of Genomic Selection With Non-additive Genetic mentioning
confidence: 77%
See 1 more Smart Citation
“…In a simulated example, Toro and Varona ( 2010 ) compared random mating vs. mate selection with a model including dominance and found advantages that ranged between 6 and 22% of the expected response. Sun et al ( 2013 ), Ertl et al ( 2014 ), and Aliloo et al ( 2017 ) have confirmed these improvements with dairy cattle data. However, its implementation in livestock populations is limited because it must be taken into account that the accuracy of the prediction of a potential mate will be low and the advantage will be only relevant when traits have a large amount of non-additive genetic variance.…”
Section: Applications Of Genomic Selection With Non-additive Genetic mentioning
confidence: 77%
“…In any case, only additive values (substitution effects) contribute to breeding values and are therefore expressed in the next generation. However, estimates of non-additive genetic effects may be of relevance because: (i) they may contribute to increasing the accuracy of prediction of breeding values and the response to selection (Toro and Varona, 2010 ; Aliloo et al, 2016 ; Duenk et al, 2017 ); (ii) they allow the definition of mate allocation procedures between candidates for selection (Maki-Tanila, 2007 ; Toro and Varona, 2010 ; Aliloo et al, 2017 ); and (iii) they can be used to benefit from non-additive genetic variation through the definition of appropriate crossbreeding or purebred breeding schemes (Maki-Tanila, 2007 ; Zeng et al, 2013 ).…”
Section: Genomic Selectionmentioning
confidence: 99%
“…This method is useful as it makes the genomic relationship matrices analogous to the pedigree-based numerator relationship matrices, allowing for a direct comparison of genomic-based estimates of variance components with the pedigree-based counterparts. It has been suggested that the dominance variance could be over-estimated if the average effects of inbreeding depression are not accounted for in the models (Aliloo et al, 2017). Therefore, we also investigated the effect of fitting animal's inbreeding coefficient as a covariate when estimating variance components.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of dominance in genomic evaluation models has been proposed by several authors (Su et al 2012;Vitezica et al 2013Vitezica et al , 2016Ertl et al 2014;Muñoz et al 2014;Aliloo et al 2016Aliloo et al , 2017Xiang et al 2016). In those studies, additive and dominant marker effects ða and dÞ are considered uncorrelated.…”
mentioning
confidence: 99%